2020
DOI: 10.1101/2020.12.03.410761
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

V-NeuroStack: 3D Time Stacks for Identifying Patterns in Calcium Imaging Data

Abstract: BackgroundUnderstanding functional correlations between the activities of neuron populations is vital for the analysis of neuronal networks. Analyzing large-scale neuroimaging data obtained from hundreds of neurons simultaneously poses significant visualization challenges. We developed V-NeuroStack, a novel network visualization tool to visualize data obtained using calcium imaging of spontaneous activity of cortical neurons in a mouse brain slice.New MethodV-NeuroStack creates 3D time stacks by stacking 2D ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Compared to the most commonly used technique for large-scale brain imaging, fMRI with BOLD signals, where the voxel sizes range from millimeters in humans to hundreds of microns in rats, the current analysis provides substantially higher spatial resolution. In addition, we have recently applied CommDy to calcium imaging data from cortical slices and observed that CommDy is able to detect known features of cortical connectivity ( Naik et al, 2019 ). Therefore, it is likely that the current analytical approach may be adapted to any of the imaging techniques mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the most commonly used technique for large-scale brain imaging, fMRI with BOLD signals, where the voxel sizes range from millimeters in humans to hundreds of microns in rats, the current analysis provides substantially higher spatial resolution. In addition, we have recently applied CommDy to calcium imaging data from cortical slices and observed that CommDy is able to detect known features of cortical connectivity ( Naik et al, 2019 ). Therefore, it is likely that the current analytical approach may be adapted to any of the imaging techniques mentioned above.…”
Section: Discussionmentioning
confidence: 99%